Conversations about adult learning in our complex world - Boden, Carrie J.; King, Kathleen P.; Merritt, Lauren (Adult education special topics., 2013)
We recognize that our society and demands for lifelong learning changes rapidly, and needs to continue to be rapidly effectively infused in changing forms into the teaching and learning process. Conversations about Adult Learning in Our Complex World focuses the study of adult learning to address the issues of living and learning within a complex world- the epitome of the 21st century.Readers will find that this book is valuable for a wide variety of professors, researchers, practitioners, and students in fields related to adult learning and adult education as it reveals emerging research and trends relevant for today and tomorrow. Moreover, this publication represents some of the most innovative and thoughtful scholarship resulting from the work of the Adult Higher Education Alliance and, arguably, the field of adult education.The book is arranged thematically in five sections, each one dealing with a domain where intercultural competence and other fundamental skills may improve the learning experiences for adult learners. The sections include, The Learning Environment and Authentic Teaching, Interculturally Competent Classroom Practices, Programming for Adults--Redesigning University to Serve Adult Learners, Professional Development, Teacher Training, and Leadership Development, and Meaningful Assessment of Programs for Adults.